Regional autonomy and its impact on madrasah education - Dahlena Sari Marbun (Proceedings of AICS - Social Sciences, 2013)
The appearance of regional autonomy policy and decentralization in education aims to provide opportunities to educational participants to obtain skills, knowledge, and attitude which are useful to society. Madrasah could respond to to sudden change in curriculum as it does not exactly follow the national curriculum. As an educational institution born out of societal needs, madrasah integration in society is easier, as the society participates more in madrasah operation. The involvement of society is not only limited based to parents involvement, but also the wider societal involvement. As in accordance with the spirit of decentralization which takes in aspiration and participation of society, the involvement of society at large is needed to develop and improve madrasah educational quality.Keywords: Autonomy, education, Islamic